Guideline-directed medical therapy after transcatheter edge-to-edge mitral valve repair. Issue 21 (7th June 2022) - Tanaka, Tetsu; Kavsur, Refik; Spieker, Maximilian; Iliadis, Christos; Metze, Clemens; Brachtendorf, Birthe M; Horn, Patrick; Zachoval, Christian; Sugiura, Atsushi; Kelm, Malte; Baldus, Stephan; Nickenig, Georg; et al.
Abstract : Objective: A sizeable proportion of patients with secondary mitral regurgitation (SMR) do not receive guideline-directed medical therapy (GDMT) for heart failure (HF). We investigated the association between the use of GDMT and mortality in patients with SMR who underwent transcatheter edge-to-edge repair (TEER). Methods: We retrospectively analysed patients with SMR and a left ventricular ejection fraction of <50% who underwent TEER at three centres. According to current HF guidelines, GDMT was defined as triple therapy consisting of beta-blockers, renin–angiotensin system (RAS) inhibitors and mineralocorticoid receptor antagonists (MRAs). Patients were divided into two groups: GDMT and non-GDMT groups. We calculated the propensity scores and carried out inverse probability of treatment weighting (IPTW) analyses to compare 2-year mortality between the two groups. Results: Of 463 patients, 228 (49.2%) were treated with GDMT upon discharge. IPTW-adjusted Kaplan-Meier curve showed patients with GDMT had a lower incidence of mortality than those without GDMT (19.8% vs 31.1%, p=0.011). In IPTW-adjusted Cox proportional hazards analysis, GDMT was associated with a reduced risk of 2-year mortality (HR: 0.58; 95% CI: 0.35 to 0.95; p=0.030), which was consistent among clinical subgroups. Moreover, patients with GDMT had a higher rate of left ventricular reverse remodelling at 1 year after TEER than those without GDMT. Conclusion: GDMT, defined as triple therapy consisting of beta-blockers, RAS inhibitors and MRAs, was associated with a reduced risk of 2-year mortality after TEER for SMR. Optimisation of medical therapy is crucial to improve clinical outcomes in patients undergoing TEER for SMR.